DOA PUASA DI ANTARA KEPEMIMPINAN PENGGEMBALAAN, ROH KUDUS, DAN PERTUMBUHAN GEREJA - Sewie Elia Huang (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2020)
Abstract Fasting prayer has a very significant role for the growth of faith and congregation in the growth of the church because fasting prayer is their intimate relationship with God. The purpose of this paper answers the question: What is meant by fasting prayer? What is the relationship between fasting prayer and the Holy Spirit? What is the relationship between fasting prayer and shepherding leadership? What is the relation of fasting prayer in the growth of the Church? The research method uses descriptive literature research. The results of the study are: (1) fasting prayer is abstaining from all physical food for other bodies describing the consequences of fasting, namely: "suffering of the soul". (2) the relationship of fasting prayer with the Holy Spirit is fasting prayer which brings clarity of the way, the voice of the spirit, so that it will be sensitive to the voice of the Holy Spirit to provide guidance in obtaining spiritual and material victory as well. (3) the relationship of fasting prayer with the leadership of the shepherding is a servant of God who truly is a servant of God whose life of prayer is accompanied by fasting. (4) the relation of fasting prayer in the growth of the Church is the pastoral service can help realize the need for maturity and encourage growth in spirituality.AbstrakDoa puasa mempunyai peran yang sangatlah signifikan bagi pertumbuhan iman dan jemaatnya dalam pertumbuhan gereja karena doa puasa merupakan hubungan intim mereka dengan Allah. Tujuan penulisan ini menjawab pertanyaan: Apakah yang dimaksud dengan doa puasa? Bagaimanakah relasi doa puasa dengan Roh Kudus? Bagaimanakah relasi doa puasa dengan kepemimpinan pengembalaan? Bagaimanakah relasi doa puasa dalam pertumbuhan Gereja? Metode penelitian menggunakan penelitian deskriptif literature. Hasil penelitian adalah: (1) doa puasa adalah berpantang dengan semua makanan jasmani untuk tubuh yang lain menggambarkan akibat berpuasa, yaitu: “penderitaan jiwa”. (2) relasi doa puasa dengan Roh Kudus adalah doa puasa mendatangkan kejernihan jalan, akan suara roh, sehingga akan peka dengan suara Roh Kudus untuk memberikan bimbingan memperoleh kemenangan rohani dan materi juga. (3) relasi doa puasa dengan kepemimpinan pengembalaan adalah seorang hamba Tuhan yang sungguh sungguh adalah hamba Tuhan yang hidup doanya disertai puasa. (4) relasi doa puasa dalam pertumbuhan Gereja adalah pelayanan penggembalaan dapat menolong menyadari kebutuhan akan kedewasaan dan mendorong bertumbuh dalam kerohanian.